Batch thermosonication for the reduction of plasmin activity in skim milk. Issue 5 (25th March 2018) - Annandarajah, Cindu; Grewell, David; Talbert, Joey N.; Raman, D. Raj; Clark, Stephanie
Abstract: The effect of batch thermosonication at 20 kHz on plasmin activity in skim milk, stored up to 49 days, was studied. The influence of sonication time was evaluated by heating samples to 72°C for 15 s, followed by sonication at 72 °C, at a constant amplitude of 170 µmpeak‐to‐peak (p–p) for 10, 30, or 60 s. The influence of temperature was evaluated by sonicating samples for 60 s at 15, 30, 45, 60 and 75°C at constant amplitude. Plasmin activity of treated as well as raw and heated control samples were analyzed on days 7, 21, 35, and 49. At all three times tested, thermosonication significantly decreased the plasmin activity compared to the raw and heated controls, with plasmin activity being reduced by over 90% after the 60 s treatment. Across the evaluated temperature range, samples that were thermosonicated displayed lower plasmin activity than their counterparts that were heated without sonication. Practical applications: In this study, batch thermosonication was explored as a means to reduce plasmin activity in skim milk. As protease activity can lead to adverse textural changes and off‐flavor development in milk, a reduction of plasmin activity is expected to enhance the quality of milk as a function of time. Results from this study suggest batch thermosonication can reduce plasmin activity, which indicates the potential of the method to extend the shelf life of skim milk.